2009
DOI: 10.1111/j.1360-0443.2009.02532.x
|View full text |Cite
|
Sign up to set email alerts
|

An analysis of cocaine powder in the Netherlands: content and health hazards due to adulterants

Abstract: An increase in adulterants was detected in the analysed cocaine powder between 1999 and 2007. This increase is associated with relatively more adverse effects with cocaine use. The cardiac and hallucinatory effects that were reported more frequently are not understood clearly. Adverse effects are likely to be due to several factors, including interactions of adulterants with cocaine and the route of administration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
57
0
3

Year Published

2010
2010
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 84 publications
(61 citation statements)
references
References 31 publications
1
57
0
3
Order By: Relevance
“…Nowadays levamisole is almost only used in veterinary medicine as an anthelminthic, but recently, it has been found to be an adulterant of seized cocaine in several countries (USA [1], Canada [2], the Netherlands [3], Italy [4] and Spain [5] among others). It is supposed to be added to cocaine in order to enhance its euphoric effects, as it is believed to inhibit dopamine reuptake in presynaptic terminals of neurons [6].…”
Section: Discussionmentioning
confidence: 99%
“…Nowadays levamisole is almost only used in veterinary medicine as an anthelminthic, but recently, it has been found to be an adulterant of seized cocaine in several countries (USA [1], Canada [2], the Netherlands [3], Italy [4] and Spain [5] among others). It is supposed to be added to cocaine in order to enhance its euphoric effects, as it is believed to inhibit dopamine reuptake in presynaptic terminals of neurons [6].…”
Section: Discussionmentioning
confidence: 99%
“…Similar results have been observed elsewhere in Italy [18], and the rest of Europe [19], though the true percentage is not known. Levamisole now permeates the U.S. cocaine supply [3,7,9,11,12,[20][21][22][23][24][25], and there may well be a medical price to pay. …”
Section: Levamisole-adulterated Cocainementioning
confidence: 99%
“…However, the authors of the Dutch report also observed that cardiac and hallucinatory effects in that region's cocaine abusers were, for no apparent reason, being reported more frequently. They suggested that the adverse effects might have been due to some unrecognized adulterant [3]. These speculations were followed five years later by controlled studies demonstrating the equine conversion of levamisole to aminorex [4].…”
Section: Introductionmentioning
confidence: 96%
“…The term “crack” is derived from the audible crackling noise produced when this form is heated as it is smoked. Street forms of cocaine may contain adulterants such as sugar, and anesthetics like lidocaine and benzocaine (Fucci & De Giovanni, 1998) (McKinney et al, 1992) and other adulterants (Evrard et al, 2010) (Brunt et al, 2009). Of particular concern is the recent finding that nearly 70% of seized cocaine entering the USA contains detectable amounts of the agranulocytosis-inducing, anti-helminthic drug, levamisole.…”
Section: Introductionmentioning
confidence: 99%